The European Commission's Scoreboard of Macroeconomic Imbalances – The Impact of Preferences on an Early Warning System - Tobias Knedlik (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2012)
The European Commission's Scoreboard of Macroeconomic Imbalances is a rare case of a publicly released early warning system (EWS). That allows for analyzing the preferences of the involved politicians with regard to the two potential errors of an EWS - missing a crisis and issuing a false alarm. This is done for the first time for EWS in general by using a standard signals approach including a preference-based optimization approach to set thresholds. It is shown that in general, the thresholds of the scoreboard are set low (resulting in more alarm signals) as compared to a neutral stand. – – Das Scoreboard der Europäischen Kommission zu makroökonomischen Ungleichgewichten ist ein seltenes Beispiel für ein veröffentlichtes Frühwarnsystem. Es ermöglicht die Analyse von Präferenzen der involvierten Politiker bezüglich möglicher Fehler in einem Frühwarnsystem - eine Krise zu verpassen oder falschen Alarm auszulösen. Diese Untersuchung wird hier zum ersten Mal für Frühwarnsysteme insgesamt durchgeführt. Dazu wird eine Standardmethode, ein Signalansatz mit einem präferenzbasierten Optimierungsansatz zur Bestimmung von Schwellenwerten verwendet. Es wird gezeigt, dass die Schwellenwerte des Scoreboards im Allgemeinen recht niedrig angesetzt werden, was sich im Vergleich zu einer neutralen Position in mehr Krisensignalen ausdrückt.
urn:nbn:de:101:1-201212176879
Keywords: G01; F47; F53; 330; early warning system; scoreboard; preferences; incentives; political economy; Frühwarnsysteme; Scoreboard; Präferenzen; Anreize; Politische Ökonomie